2020
DOI: 10.1021/acs.joc.0c01940
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Induced Dehydrogenative Imidoylation of Imidazo[1,2-a]pyridines with α-Amino Acid Derivatives and α-Amino Ketones

Abstract: A new and efficient visible-light-promoted dehydrogenative cross-coupling reaction of imidazo­[1,2-a]­pyridines with α-amino carbonyl compounds toward imidoyl imidazo­[1,2-a]­pyridines is developed. A diverse range of imidazo­[1,2-a]­pyridines undergoes the dehydrogenative imidoylation smoothly with α-amino carbonyl compounds to access the corresponding products in satisfactory yields. We have also proposed the possible reaction mechanism based on preliminary mechanistic studies. The synthetic method has the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…The same authors recently extended their synthetic method by coupling imidazo[1,2- a ]pyridines with α-amino ketones and α-amino acid derivatives [ 56 ]. Some improvements were applied: the metal catalyst was replaced by an organophotocatalyst (Eosin Y), with citric acid monohydrate as an additive.…”
Section: C–h Functionalizationmentioning
confidence: 99%
“…The same authors recently extended their synthetic method by coupling imidazo[1,2- a ]pyridines with α-amino ketones and α-amino acid derivatives [ 56 ]. Some improvements were applied: the metal catalyst was replaced by an organophotocatalyst (Eosin Y), with citric acid monohydrate as an additive.…”
Section: C–h Functionalizationmentioning
confidence: 99%
“…Jiangxi Province Key Laboratory of Synthetic Chemistry, East China University of Technology, Nanchang, 330013, China. E-mail: zbxie@ecut.edu.cn visible light has a wide range of practical applications in the fields of organic synthetic chemistry [36][37][38][39][40][41] and photocatalytic composite materials. 42,43 Inspired by recent photochemical studies, we report a new approach for the green synthesis of quinazolinones using benzyl bromide and 2-aminobenzamide under mild conditions without additives, oxidants, or catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, visible light has been successfully utilized as a clean energy source with high sustainability and environmental friendliness. Researchers have found that visible light has a wide range of practical applications in the fields of organic synthetic chemistry 36–41 and photocatalytic composite materials. 42,43 Inspired by recent photochemical studies, we report a new approach for the green synthesis of quinazolinones using benzyl bromide and 2-aminobenzamide under mild conditions without additives, oxidants, or catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[12a] Later same group developed imination of imidazo[1,2-a]pyridines under visible light conditions [12b] (Figure 2). [12][13][14][15][16] On the other hand, α-imino ketones are excellent building blocks in organic synthesis for constructing various nitrogencontaining molecules. [17] Fascinated by their simple preparation methods and versatile reactivity, several groups, including us, have utilized them as excellent precursors in synthetic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, Zhu et al., reported a visible‐light‐promoted cross‐dehydrogenative‐coupling reaction of N ‐arylglycine esters with imidazo[1,2‐ a ]pyridines to get α‐aryl‐glycine esters [12a] . Later same group developed imination of imidazo[1,2‐ a ]pyridines under visible light conditions [12b] (Figure 2). [12–16]…”
Section: Introductionmentioning
confidence: 99%